1969
DOI: 10.1139/g69-076
|View full text |Cite
|
Sign up to set email alerts
|

INHERITANCE IN HEXAPLOID WHEAT OF LEAF RUST RESISTANCE AND OTHER CHARACTERS DERIVED FROM AEGILOPS SQUARROSA

Abstract: T h e inheritance of seedling leaf rust resistance and several morphological characters derived from Aegilops sqzlnrrosn (211 = 14 = D D ) was investigated in a synthetic hexaploid wheat. T h c hexaploid was obtained by combining the tetraploid component (211 = 28 = A A B R ) extracted from thc colnmon whcat cultivar Canthatch with Ae. sqzlnrrosn 1 ar. nreyeri R.L. 5289.A major, partially dominant gene was identified that gives good resistance (typc 0;l rcaction) t o leaf rust races 1, 5, 9, 11, 15, 30, 58 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
50
1

Year Published

1980
1980
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(59 citation statements)
references
References 7 publications
8
50
1
Order By: Relevance
“…However, numerous studies in Triticum have revealed that the expression of resistance is reduced when genes are transferred from lower to higher ploidy levels. This phenomenon of a 'dilution' of the resistance was reported by Kerber & Dyck (1969, 1979 for leaf rust, Trottet et at. (1982) for leaf and stripe rust, mildew and glume blotch, Gill et al (1986) for leaf rust, mildew, greenbug and Hessian fly, Chevre et a!.…”
Section: Introductionsupporting
confidence: 61%
“…However, numerous studies in Triticum have revealed that the expression of resistance is reduced when genes are transferred from lower to higher ploidy levels. This phenomenon of a 'dilution' of the resistance was reported by Kerber & Dyck (1969, 1979 for leaf rust, Trottet et at. (1982) for leaf and stripe rust, mildew and glume blotch, Gill et al (1986) for leaf rust, mildew, greenbug and Hessian fly, Chevre et a!.…”
Section: Introductionsupporting
confidence: 61%
“…The dilution of leaf rust resistance was noted in amphiploids with T. durum when compared with the diploid resistant parent (Ae. tauschii) (Kerber and Dyck, 1969). The same also has been noted by Trottet et al (1982) with powdery mildew, leaf rust, yellow rust and glume blotch.…”
Section: Discussionsupporting
confidence: 81%
“…In their successful attempts, Kerber and Dyck (1969) and Dyck and Kerber (1970) could transfer the genes for leaf rust resistance to common wheat from two strains of Ae, squarrosa of KUSE collection. These are the practical examples demonstrating rather easy transfer of the desirable gene to common wheat from its wild relatives through genetic recombination.…”
Section: Introductionmentioning
confidence: 99%